Strategi BUMDes Guyub Rukun dalam Pemberdayaan Masyarakat Desa Wringinputih, Kecamatan Borobudur, Kabupaten Magelang - Rachmavianti, Nafiza; Lestari, Eny; Permatasari, Putri (Balai Pelatihan Pertanian Jambi, 2024)
One of the steps in development to alleviate poverty is the presence of BUMDes. Wringinputih Village is a village in Borobudur District which has a BUMDes named BUMDes Guyub Rukun. The establishment of BUMDes aims to manage the existing potential of the village. This management requires the intensive role of BUMDes Guyub Rukun by optimizing natural resources and human resources through community empowerment so that there will be an increase in terms of community knowledge and skills. The success of community empowerment can be achieved through strategies implemented by BUMDes. The purpose of this study is to analyze the strategy of BUMDes in increasing community empowerment. The basic method of this study is qualitative descriptive by purposively determining informants sampling and snowball sampling. Data collection techniques by means of in-depth interviews, observations, and documentation and using Miles and Huberman's data analysis techniques. Data validity using source triangulation and techniques. The informants in the study were 28 people. The research results show that the strategies used by BUMDes in improving community empowerment are the possibility, strengthening, protection, support, and maintenance. Possible strategies are obervation and socialization to society. The reinforcement strategy is to conduct training and provide modalities. The protection strategy is to provide assistance. The strategy that was carried out was to open a new job field. Maintenance strategies are to conduct evaluation and monitoring.